An algorithm for least squares projections onto the intersection of translated, convex cones - Dykstra, Richard L.; Boyle, James P. (Journal of statistical planning and inference, 1986)
A commonly occurring problem is that of minimizing least squares expressions subject to restrictions on the solution. Dykstra (1983) has given a simple algorithm for solving these types of problems when the constraint region can be expressed as a finite intersection of closed, convex cones. Here it is shown that this algorithm must still work correctly even when each cone is allowed to be arbitrarily translated, as long as the intersection is nonempty. This allows the algorithm to be applied to a much larger collection of problems than previously indicated.